School and Parents Partnership in Improving Student Achievement at Primary School (SD) Plus Muhammadiyah 1 Waru Pamekasan - Fauzan, Fauzan; Ulfatin, Nurul; Arifin, Imron; Sobri, Ahmad Yusuf; Imamuddin, Imamuddin (EDUKASIA, 2025)
The partnership between schools and parents plays a significant role in creating a conducive learning environment, fostering an enjoyable atmosphere both at school and at home. This study investigates the impact of school-parent partnerships on enhancing student achievement, utilizing a qualitative case approach. Data were collected through interviews, observations, and documentation. Two key findings about the school-parent partnership at SD Plus Muhammadiyah 1 Waru were identified. First, the school involves parents through various communication mechanisms: routine meetings, parenting sessions, home visits, parent associations, social media for information and communication, school committee engagement, violation control cards, daily monitoring books, and formal letters. Second, parents respond to school programs by integrating school and home learning activities, attending school events, providing necessary information during teacher visits, staying updated through social media, actively participating in communication groups, and monitoring student activities through the provided tools. The collaboration and synergy between school and home learning activities contribute significantly to fostering a positive and effective learning environment for students. This study will show other schools how important structured parent-school partnerships are, especially when combined with culturally relevant approaches. They will provide a replicable framework for improving student learning outcomes and professional school management.